Microbial Safety of Low Water Activity Foods: Study of Simulated and Durban Household Samples - O. A. Ijabadeniyi; Y. Pillay (Journal of Food Quality)
Sixty household low water activity foods were examined and a simulative study was conducted in a high sugar, low aw almond and macadamia butter to determine the survival of Bacillus cereus and Staphylococcus aureus ATCC 25923. Results obtained from 60 low aw samples collected at household level had some significant differences (P≤0,05) within food categories amongst the various tests. Spices had the highest number of aerobic bacteria, aerobic spore-formers, anaerobic spore-formers, and S. aureus. Mean aerobic colony counts for nuts and spices were 2.30 log CFU/g and 4.40 log CFU/g, respectively. Pathogens such as Escherichia coli and Cronobacter sakazakii were present in nuts, whilst Salmonella spp. was present in chocolates. This implies that certain low aw foods may present a public health risk. In the simulative study, temperature and high sucrose concentrations played a significant role in the survival of B. cereus and S. aureus ATCC 25923. B. cereus was found to be more osmotolerant at both reduced and elevated temperatures (18°C and 25°C) in the 12% sucrose sample in both butters, whilst S. aureus ATCC 25923 seemed to grow better in sucrose-free samples at both temperatures in both butters. This implies that certain low aw foods may present a public health risk. Also, B. cereus, being a spore-forming bacterium, can be osmotolerant at both reduced and elevated temperatures.